Evaluating the Efficacy of Vasthi in Benign Prostatic Hyperplasia: A Case Study - Wijesiriwardhana, H.G.S.G.; Peshala, K.K.V.S. (University of Colombo, 2024)
Benign prostate hyperplasia is a histological diagnosis characterized by the proliferation of smooth muscle and epithelial cells within the transient zone of prostate gland. The incidence and severity of lower urinary tract symptoms due to benign prostate hyperplasia are increasing day by day and more likely to occur in after 40 years of age. Due to the resemblance of clinical feature, it is often correlated with Asthila, a type of Mutraghata according to all the Acharyas. The objective of this study was to evaluate the effectiveness of an Ayurveda treatment in benign prostate hyperplasia. A male patient presented at the OPD of District Ayurveda Hospital, Bibila, Medagama where he was diagnosed with Asthila based on clinical features and an abdomical ultra sound scan. The patient was treated with local Sneha karma (application of oil) using Hingu thriguna oil, and Sweda with Dashamool nadi sweda followed by Yoga vasthi with Punaenawashtaka kwatha (480ml). Herbal decoctions and Vasti were administered orally for 28 days. Patient assessment was conducted using International Prostate Symptom Score (IPSS), prostate weight, and post void residual urine volume. After completion of Vasthi treatment, significant relief was observed in symptoms. The IPSS score was decreased from 13 before treatment to three after treatment. The volume of the prostate reduced from 26cc to 16cc. This study conclusively demonstrated the effectiveness of Punarnawashtaka niruha vasti with favorable results supporting further studies to evaluate the efficacy of this regime
Keywords: Asthila; Benign Prostate Hyperplasia; Punarnawashtaka Niruha Vasthi